Participação dos canais para potássio nos efeitos cardiovasculares induzidos por um novo composto 1,3,4- oxadiazol. - Reis, Milena Ramos (2012)
It was observed the pharmacological effects of OXDINH, a 1,3,4-oxadiazole derivative obtained by organic synthesis, on the cardiovascular system and the involvement of K+ channels in this response, were studied in rats using techniques combined in vivo and in vitro. In the superior mesenteric artery rings isolated from rats with functional endothelium, OXDINH (10-10 - 10-4 M) induced relaxation of contractions induced by phenylephrine (1 μM) (pD2 = 5.33 ± 0.16, Emax = 117.03 ± 6.49%, n = 7) concentration dependent manner and this effect was not attenuated after removal of the vascular endothelium (pD2 = 5.15 ± 0.09; Emáx = 108.58 ± 6.03%, n = 6). These results suggest that the response induced by vasorelaxant OXDINH seems to be independent of the vascular endothelium. Based on these initial observations, the subsequent experiments were performed with preparations without endothelium. In the preparations incubated with KCl 20mM, a modulator of the efflux of K+, the vasorelaxant effect induced OXDINH was changed (pD2 = 4.67 ± 0.08; Emáx = 57.71 ± 1.72%, n = 5), which is a characteristic of substances that act by activating K+ channels. This effect was corroborated after the use of tetraethylammonium (TEA) 3 mM (Emáx = 44.26 ± 2.41%) that this concentration does not selectively block K+ channels. In addition, the vasodilating effect OXDINH was significantly attenuated after incubation with 4- aminopyridine (1 mM) (Emáx = 61.17 ± 5.55%), glibenclamide (10 μM) (Emáx = 57.00 ± 4.07%), or BaCl2 (30 μM) (Emáx = 61.87 ± 7.52%), selective blockers of KV, KATP and KIR, respectively. By using TEA (1 mM), which at this concentration is more selective for the BKCa, vasodilatation was also found to be significantly attenuated (Emáx = 47.31 ± 5.75%), suggesting the involvement of these channels in this effect. Additionally, when OXDINH (10-5 and 10-4 M) was incubated in depolarizing medium nominally without Ca2+, CaCl2 induced contractions were not changed. However, these contractions were significantly attenuated concentration dependent manner when OXDINH (10-4 M) was incubated in saline without Ca2+ and nominally in the presence of phenylephrine (10μM). In non-anesthetized normotensive rats, OXDINH (1, 5 and 10 mg.kg-1 iv, randomly) produced hypotension accompanied by tachycardia. Interestingly, the highest dose (30 mg.kg-1) of OXDINH, the pressor and tachycardic response was, probably by a direct effect of the compound in the heart. In conclusion, these results suggest that the biological effects induced by OXDINH seem to directly involve the participation of K+ channels, probably by repolarization / hyperpolarization of the membrane and consequent closure of Cav, preventing the influx of Ca2+ through these channels.